Littered cigarette butts in both coastal and inland cities of China: occurrence and environmental risk assessment - Yang, Qiying; Zhong, Weibin; Jiao, Yaqian; Zhang, Yuan; Cheng, Liuling; Ruan, Yifan; Yang, Shanshan (Frontiers in Marine Science, 2024)
Cigarette butts (CBs) pollution is a critical global environmental issue, yet limited research exists on CBs pollution in both coastal and inland Chinese cities with varying development levels. This study investigated CBs occurrence, contamination, Cigarette Butts Pollution Index (CBPI), and heavy metal leakage in four cities. The results of CBs collected over multiple days revealed higher contamination levels in coastal city of Dalian (0.10 ± 0.03 CBs/m2), inland cities of Baoding (0.06 ± 0.02 CBs/m2) and Meizhou (0.07 ± 0.02 CBs/m2) compared to first-tier coastal city of Guangzhou (0.03 ± 0.02 CBs/m2). Patterns of CBs occurrence and CBPI varied across land usage and cities development level. SEM and EDS analysis identified microplastics and heavy metal particles released from CBs in water environments. ICP-MS detected a total of 629.7 μg/L of 14 heavy metals. Approximately 1.9 ± 0.9 g/km2 of heavy metals are leaked daily in Chinese cities due to CBs, posing a severe threat to soil and water safety given the indiscriminate disposal of CBs. This study offers scientific insights into CBs pollution and underscores the pressing need for effective measures to mitigate environmental hazards, particularly heavy metal and microplastics contamination released from CBs in China.